The effect of childhood maltreatment on non-suicidal self-injury in adolescents with bipolar disorder: the mediating role of dysfunctional attitudes and the moderating role of social support - Tan, Huawei; Zhao, Dan; Cao, Jiarui; Huang, Ting; Yi, Jiahui; Wan, Zhihui; Zhang, Fan (Frontiers in Psychiatry, 2025)
BackgroundChildhood maltreatment has been consistently associated with nonsuicidal self-injury (NSSI). Patients with bipolar disorder (BD) are especially vulnerable to early adversity and self-injurious behaviors; however, the mechanisms underlying this association remain unclear. Among Chinese patients with BD, this study tested whether dysfunctional attitudes mediate the association between childhood maltreatment and NSSI and whether social support moderates this association.MethodsA cross-sectional study was conducted with 838 clinically diagnosed bipolar disorder patients (68.1% female; median age = 16 years). Measures included the Childhood Trauma Questionnaire–Short Form (CTQ-SF), Dysfunctional Attitudes Scale (DAS-A), Social Support Rating Scale (SSRS), Ottawa Self-Injury Inventory–Chinese Revised Edition (OSIC), and Hamilton Depression Rating Scale (HAMD-24). Descriptive analyses, correlations, mediation, and moderated mediation models were tested using SPSS 26.0 and Mplus 8.3, with robust maximum likelihood estimation (MLR) and 5,000 bootstrap resamples.ResultsIn our clinical sample of patients with bipolar disorder, 68.5% reported nonsuicidal self-injury (NSSI). Childhood maltreatment was positively associated with both dysfunctional attitudes and NSSI. Mediation analysis demonstrated that dysfunctional attitudes partially mediated the association between childhood maltreatment and NSSI (indirect effect β = 0.040, 95% CI [0.017, 0.061], p < 0.01), accounting for 18.2% of the total effect. Moderation analysis further indicated that social support significantly attenuated the association between dysfunctional attitudes and NSSI (interaction β = –0.082, 95% CI [–0.162, –0.015], p < 0.05), but did not moderate the associations of childhood maltreatment with either dysfunctional attitudes or NSSI.ConclusionChildhood maltreatment increases the risk of NSSI in patients with BD both directly and indirectly through dysfunctional attitudes, while social support mitigates the behavioral impact of dysfunctional attitudes on NSSI. These findings highlight dysfunctional attitudes as a cognitive mechanism and social support as a conditional protective factor, underscoring the importance of childhood maltreatment screening, cognitive restructuring, and support-enhancing interventions in reducing NSSI risk among Chinese patients with bipolar disorder.